A preparation method of lithium pyromellitic acid

By using lithium phenyladetetrachloride as an additive preparation method in lithium-ion batteries, the problem of decomposition of traditional electrolyte at high voltage and intensification of side reactions is solved, and higher battery performance and safety are achieved.

CN118878408BActive Publication Date: 2025-03-18SHANDONG HAIHUA GRP CO LTD +1

Patent Information

Application Number
CN202411351280.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-03-18
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

The electrochemical window of traditional carbonate electrolytes is narrow and easy to decompose at high voltages, resulting in intensified side reactions, transition metal dissolution and combustion explosion risks. Existing additives such as VC are unstable at high temperatures and high voltages, affecting battery performance.

Method used

Using a preparation method of lithium phenyladium tetrachloride, lithium hydroxide reacts with ethylene glycol solution of phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium phenyladium

Benefits of technology

The preparation of lithium phenyladium phenyladium with high purity and low impurity is achieved. As a lithium battery additive, its performance under high temperature, magnification and low temperature conditions is significantly better than that of traditional VC and VC composite systems, and has higher capacity retention and discharge capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118878408B_ABST
    Figure CN118878408B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of lithium benzene tetracarboxylate, and relates to the technical field of lithium ion batteries. An ethylene glycol solution of pyromellitic acid is added with lithium hydroxide under heating and stirring conditions for reaction, the reaction solution is filtered, and the obtained solid is vacuum dried to obtain a crude lithium benzene tetracarboxylate product; the crude lithium benzene tetracarboxylate product is dissolved in ethanol under heating and stirring conditions, filtered while hot, the filtrate is decompressed and distilled, and the obtained solid is vacuum dried to obtain lithium benzene tetracarboxylate crystals. The synthesis reaction can be completed in one step by the method of the invention, the reaction is simple, no waste gas is generated, environmental protection and high yield; the lithium benzene tetracarboxylate obtained after purification has high purity and low impurity content, meets the requirements of battery grade, and the prepared lithium benzene tetracarboxylate has better performance than commonly used lithium battery additives as a lithium battery additive, and has broad industrialization prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing lithium pyrolytetracarboxylate. Background Art

[0002] At present, lithium-ion batteries have broad application prospects in portable electronic products, electric vehicles, hybrid vehicles and smart grids. Electrolyte, as a carrier of ion transmission in the battery, is the "blood" of the battery and one of the four key components of lithium batteries. It acts as a carrier for lithium ions to move between the positive and negative electrodes of lithium batteries and is one of the key factors affecting the performance of lithium batteries. The components of the electrolyte mainly include lithium salts, organic solvents and additives. Additives can improve battery performance in a targeted manner.

[0003] The electrochemical window of traditional carbonate electrolytes is narrow (<4.3 V vs. Li+ / Li). When the voltage increases, the electrolyte itself will decompose on the one hand; on the other hand, the side reaction between the positive electrode and the electrolyte intensifies, and the transition metal dissolves, further decomposing the electrolyte. A large amount of gas is generated, which is very likely to cause combustion and explosion. At present, one of the main solutions is to develop suitable electrolyte additives. Among them, vinylene carbonate (VC) is a representative of additives. It is basically used in high-voltage electrolyte formulations, and the addition amount is 1.5-3%. For a long time, the mechanism of action of VC is believed to be that during the battery formation process, it is reduced on the negative electrode surface before vinyl carbonate (EC, one of the components of the electrolyte) to form a solid electrolyte interface film (SEI). Subsequently, researchers also found the decomposition products of VC on the positive electrode surface. However, VC above 1.5% will increase the battery impedance, affecting the battery's rate performance and low-temperature performance. In addition, the VC interface film is unstable under high temperature and high voltage conditions. In practical applications, additives such as FEC, LiPO2F2, and PS are added for compound use. However, the compounded system also has disadvantages such as high-temperature instability or low-temperature efficiency.

[0004] Therefore, a new multifunctional additive is developed, which not only maintains the original advantages of VC, but also improves the disadvantages of VC, so that a single additive can exceed the effect of VC and its compound formula. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation method of lithium phenylenetetracarboxylate, which has a simple process route, is environmentally friendly, has a high product yield, high purity, and low impurity content. The present invention also evaluates lithium phenylenetetracarboxylate as a lithium battery additive, and the results show that the lithium battery additive synthesized by the present invention has better performance than the currently commonly used additives.

[0006] The preparation method of lithium pyromellitic acid tetracarboxylate of the present invention comprises the following steps:

[0007] (1) adding lithium hydroxide to a ethylene glycol solution of pyromellitic acid under heating and stirring to react, filtering the reaction solution to obtain a crude product of lithium pyromellitic acid;

[0008] The reaction equation is as follows:

[0009]

[0010] (2) The crude lithium pyroxene tetracarboxylate is dissolved in ethanol under heating and stirring conditions, filtered while hot, and the filtrate is distilled under reduced pressure. The obtained solid is vacuum dried to obtain lithium pyroxene tetracarboxylate crystals.

[0011] Preferably, in step (1), the concentration of the ethylene glycol solution of pyromellitic acid is 0.2-0.4 mol / L, the molar ratio of pyromellitic acid to lithium hydroxide is 1:3.8-4.2, the heating reaction temperature is 80-140° C., and the reaction time is 24-36 h.

[0012] More preferably, in step (1), the heating reaction temperature is 100-120° C. and the reaction time is 28-32 h.

[0013] Preferably, in step (2), the ratio of crude lithium pyrolysis acid salt to ethanol is 1 g: 10-20 ml, the heating and stirring temperature is 70°C-90°C, the time is 1-3 h, the reduced pressure distillation temperature is 60-80°C, the time is 12-20 h, the vacuum drying temperature is 70-90°C, and the vacuum drying time is 16-24 h.

[0014] The beneficial effects of the present invention are:

[0015] The lithium battery additive lithium pyroxene tetracarboxylate can be prepared by a one-step method, the reaction is simple and environmentally friendly, the yield is high, and the total yield of lithium pyroxene tetracarboxylate is >95%; the obtained lithium pyroxene tetracarboxylate has high purity (>99.9%) and low impurity content (free acid <20ppm, water <25ppm, chloride ion <3ppm, sulfate ion <4ppm). The prepared lithium pyroxene tetracarboxylate as a lithium battery additive has better performance than commonly used lithium battery additives, and the high temperature performance, rate performance and low temperature performance are significantly better than VC and VC compound system. When 1.5% of the lithium pyroxene tetracarboxylate battery of the present invention is added, the capacity retention rate after 300 cycles at 50°C is 86.1%-92.6%, the 5C discharge battery capacity is 184.3mAh / g-196.8mAh / g, and the 0.5C-20°C discharge capacity retention rate is 85.2%-89.2%, which has broad industrialization prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is the H-NMR spectrum of lithium pyromellitic acid in Example 4 of the present invention;

[0017] Figure 2 It is the thermogravimetric spectrum of lithium pyrophthalate of Example 4 of the present invention. DETAILED DESCRIPTION

[0018] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and embodiments. However, those skilled in the art will understand that the embodiments described below are part of the embodiments of the present invention, rather than all of the embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Example 1

[0019] Dissolve 1 mol of pyromellitic acid in ethylene glycol to prepare a 0.2 mol / L pyromellitic acid ethylene glycol solution. Add 3.8 mol of lithium hydroxide under stirring at 80°C, react for 24 hours, filter, and obtain crude lithium pyromellitic acid;

[0020] 100g of crude lithium pyromellitic acid was added to 1000ml of ethanol and dissolved under stirring at 70℃ for 2h, filtered while hot, and the filtrate was distilled at 60℃ for 12h under reduced pressure. The obtained solid was vacuum dried at 70℃ for 16h to obtain lithium pyromellitic acid crystals. The yield was 96%. The yield was calculated as the mass of lithium pyromellitic acid crystals (after purification): theoretically 1 mol of pyromellitic acid corresponds to the mass (yield) of lithium pyromellitic acid.

[0021] The high temperature cycle stability, rate performance and low temperature performance of lithium benzene tetracarboxylate were tested in a 4.5V NCM811 / graphite soft pack battery system. The lithium battery electrolyte solvent is 30wt% DMC+25wt% DEC, the electrolyte is lithium hexafluorophosphate, the content is 30wt%-40wt%, and the content of the additive lithium benzene tetracarboxylate is 1.5%. It was compared with the additives available on the market (1.5% VC, 1.5% VC+1.5% FEC, 1.5% VC+2% 1,3PS). In Example 1, the battery with lithium benzene tetracarboxylate added has a capacity retention rate of 87.6% after 300 cycles at 50°C, while that of Comparative Example 1, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) is only 85.2%, 73.4%, 78.5%, and 79.2%, respectively; the battery with lithium benzene tetracarboxylate added in Example 1 has a 5C discharge battery capacity of 186.5 mAh / g, while that of Comparative Example 1, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) is only 181.5 mAh / g, 152.1 mAh / g, 171.3 mAh / g, and 173.5 mAh / g, respectively; the battery with lithium benzene tetracarboxylate added in Example 1 has a capacity retention rate of 87.6% after 300 cycles at 50°C, while that of Comparative Example 1, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) is only 85.2%, 73.4%, 78.5%, and 79.2%, respectively; the battery with lithium benzene tetracarboxylate added in Example 1 has a capacity retention rate of 186.5 mAh / g at 5C discharge, while that of Comparative Example 1, Comparative Example 5 (1.5% VC), Comparative Example 6 (1. The -20℃ discharge capacity retention rate reached 85.2%, while that of Comparative Example 1, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC+1.5% FEC), and Comparative Example 7 (1.5% VC+2% 1,3PS) were only 82.6%, 65.2%, 71.4%, and 71.7%, respectively. Example 2

[0022] Dissolve 1 mol of pyromellitic acid in ethylene glycol to prepare a 0.3 mol / L pyromellitic acid ethylene glycol solution. Add 4.2 mol of lithium hydroxide under stirring at 140°C, react for 36 hours, filter, and obtain crude lithium pyromellitic acid;

[0023] 100g of crude lithium benzene tetracarboxylate was added to 2000ml of ethanol and dissolved under stirring at 90℃ for 1h, filtered while hot, and the filtrate was distilled at 80℃ for 20h under reduced pressure. The solid was vacuum dried at 90℃ for 24h to obtain lithium benzene tetracarboxylate crystals. The yield was 96%. Lithium benzene tetracarboxylate was tested for high temperature cycle stability, rate performance and low temperature performance in a 4.5V NCM811 / graphite soft pack battery system. Among them, the lithium battery electrolyte solvent was 30wt%DMC+25wt%DEC, the electrolyte was lithium hexafluorophosphate, the content was 30wt%-40wt%, and the content of the additive lithium benzene tetracarboxylate was 1.5%. And compared with the additives available on the market (1.5%VC, 1.5%VC+1.5%FEC, 1.5%VC+2%1,3PS). In Example 2, the battery with lithium benzene tetracarboxylate added has a capacity retention rate of 88.5% after 300 cycles at 50°C, while that of Comparative Example 2, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) is only 84.3%, 85.2%, 73.4%, 78.5%, and 79.2%, respectively; the battery with lithium benzene tetracarboxylate added in Example 2 has a 5C discharge battery capacity of 189.7 mAh / g, while that of Comparative Example 2, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) is only 179.3 mAh / g, 152.1 mAh / g, 171.3 mAh / g, and 173.5 mAh / g, respectively; the battery with lithium benzene tetracarboxylate added in Example 2 has a capacity retention rate of 88.5% after 300 cycles at 50°C, while that of Comparative Example 2, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) is only 84.3%, 85.2%, 73.4%, 78.5%, and 79.2%, respectively; the battery with lithium benzene tetracarboxylate added in Example 2 has a capacity retention rate of 189.7 mAh / g at 5C discharge, while that of Comparative Example 2, Comparative Example 5 (1.5% The -20℃ discharge capacity retention rate reached 86.5%, while that of Comparative Example 2, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC+1.5% FEC), and Comparative Example 7 (1.5% VC+2% 1,3PS) were only 81.5%, 65.2%, 71.4%, and 71.7%, respectively. Example 3

[0024] Dissolve 1 mol of pyromellitic acid in ethylene glycol to prepare a 0.4 mol / L pyromellitic acid ethylene glycol solution. Add 4 mol of lithium hydroxide under stirring at 100°C, react for 28 hours, filter, and obtain crude lithium pyromellitic acid;

[0025] 100 g of crude lithium pyroxetate was added to 1500 ml of ethanol and dissolved under stirring at 70°C for 1.5 h, filtered while hot, and the filtrate was distilled under reduced pressure at 70°C for 16 h. The obtained solid was vacuum dried at 80°C for 20 h to obtain lithium pyroxetate crystals. The yield was 98%.

[0026] The high temperature cycle stability, rate performance and low temperature performance of lithium benzene tetracarboxylate were tested in a 4.5V NCM811 / graphite soft pack battery system. The lithium battery electrolyte solvent is 30wt% DMC+25wt% DEC, the electrolyte is lithium hexafluorophosphate, the content is 30wt%-40wt%, and the content of the additive lithium benzene tetracarboxylate is 1.5%. It was compared with the additives available on the market (1.5% VC, 1.5% VC+1.5% FEC, 1.5% VC+2% 1,3PS). In Example 3, the battery with lithium benzenetetracarboxylate added has a capacity retention rate of 91.3% after 300 cycles at 50°C, while the capacity retention rate of Comparative Example 3, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) is only 85.5%, 85.2%, 73.4%, 78.5%, and 79.2%, respectively; the battery with lithium benzenetetracarboxylate added in Example 3 has a 5C discharge battery capacity of 195.9 mAh / g, while the capacity retention rate of Comparative Example 3, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) is only 180.9 mAh / g, 152.1 mAh / g, 171.3 mAh / g, and 173.5 mAh / g, respectively; the battery with lithium benzenetetracarboxylate added in Example 3 has a 0.5C discharge battery capacity of 195.9 mAh / g, while the capacity retention rate of Comparative Example 3, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) is only 180.9 mAh / g, 152.1 mAh / g, 171.3 mAh / g, and 173.5 mAh / g, respectively The -20℃ discharge capacity retention rate reached 88.6%, while that of Comparative Example 3, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC+1.5% FEC), and Comparative Example 7 (1.5% VC+2% 1,3PS) were only 82.4%, 65.2%, 71.4%, and 71.7%, respectively. Example 4

[0027] Dissolve 1 mol of pyromellitic acid in ethylene glycol to prepare a 0.2 mol / L pyromellitic acid ethylene glycol solution. Add 4 mol of lithium hydroxide under stirring at 120°C, react for 32 hours, filter, and obtain crude lithium pyromellitic acid;

[0028] 100 g of crude lithium pyroxetate was added to 1600 ml of ethanol and dissolved under stirring at 90°C for 3 hours, the filtrate was distilled under reduced pressure at 80°C for 16 hours, and the obtained solid was vacuum dried at 75°C for 18 hours to obtain lithium pyroxetate crystals with a yield of 99%.

[0029] The high temperature cycle stability, rate performance and low temperature performance of lithium benzene tetracarboxylate were tested in a 4.5V NCM811 / graphite soft pack battery system. The lithium battery electrolyte solvent is 30wt% DMC+25wt% DEC, the electrolyte is lithium hexafluorophosphate, the content is 30wt%-40wt%, and the content of the additive lithium benzene tetracarboxylate is 1.5%. It was compared with the additives available on the market (1.5% VC, 1.5% VC+1.5% FEC, 1.5% VC+2% 1,3PS). In Example 4, the battery with lithium benzene tetracarboxylate added has a capacity retention rate of 92.6% after 300 cycles at 50°C, while the capacity retention rates of Comparative Example 4, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) are only 83.8%, 73.4%, 78.5%, and 79.2%, respectively; the battery with lithium benzene tetracarboxylate added in Example 4 has a 5C discharge battery capacity of 196.8 mAh / g, while the capacity retention rates of Comparative Example 4, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) are only 178.4 mAh / g, 152.1 mAh / g, 171.3 mAh / g, and 173.5 mAh / g, respectively; the battery with lithium benzene tetracarboxylate added in Example 4 has a 0.5C discharge battery capacity of 196.8 mAh / g, while the capacity retention rates of Comparative Example 4, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) are only 178.4 mAh / g, 152.1 mAh / g, 171.3 mAh / g, and 173.5 mAh / g, respectively. The -20℃ discharge capacity retention rate reached 89.2%, while that of Comparative Example 4, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC+1.5% FEC), and Comparative Example 7 (1.5% VC+2% 1,3PS) were only 81.3%, 65.2%, 71.4%, and 71.7%, respectively. Example 5

[0030] Dissolve 1 mol of pyromellitic acid in ethylene glycol to prepare a 0.4 mol / L pyromellitic acid ethylene glycol solution. Add 4.1 mol of lithium hydroxide under stirring at 110°C, react for 34 hours, filter, and obtain crude lithium pyromellitic acid;

[0031] 100 g of crude lithium pyroxetate was added to 1800 ml of ethanol and dissolved under stirring at 80°C for 2.5 hours, filtered while hot, and the filtrate was distilled under reduced pressure at 65°C for 15 hours. The obtained solid was vacuum dried at 85°C for 22 hours to obtain lithium pyroxetate crystals. The yield was 97%.

[0032] The high temperature cycle stability, rate performance and low temperature performance of lithium benzene tetracarboxylate were tested in a 4.5V NCM811 / graphite soft pack battery system. The lithium battery electrolyte solvent is 30wt% DMC+25wt% DEC, the electrolyte is lithium hexafluorophosphate, the content is 30wt%-40wt%, and the content of the additive lithium benzene tetracarboxylate is 1.5%. It was compared with the additives available on the market (1.5% VC, 1.5% VC+1.5% FEC, 1.5% VC+2% 1,3PS). The battery of Example 5 with lithium benzene tetracarboxylate added has a capacity retention rate of 88.4% after 300 cycles at 50°C, while that of Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC+1.5% FEC), and Comparative Example 7 (1.5% VC+2% 1,3PS) is only 73.4%, 78.5%, and 79.2%, respectively; the battery of Example 5 with lithium benzene tetracarboxylate added has a 5C discharge capacity of 185.2 mAh / g, while that of Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC+1.3PS) is only 185.2 mAh / g. 5% FEC), Comparative Example 7 (1.5% VC+2% 1,3PS) are only 152.1mAh / g, 171.3mAh / g, and 173.5mAh / g, respectively; the 0.5C-20℃ discharge capacity retention rate of the battery in Example 5 with the addition of lithium phenyltetracarboxylate reaches 87.3%, while that of Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC+1.5% FEC), and Comparative Example 7 (1.5% VC+2% 1,3PS) are only 65.2%, 71.4%, and 71.7%, respectively. Example 6

[0033] Dissolve 1 mol of pyromellitic acid in ethylene glycol to prepare a 0.3 mol / L pyromellitic acid ethylene glycol solution. Add 3.9 mol of lithium hydroxide under stirring at 130°C, react for 30 hours, filter, and obtain crude lithium pyromellitic acid;

[0034] 100 g of crude lithium pyroxetate was added to 1400 ml of ethanol and dissolved under stirring at 75°C for 2 hours, filtered while hot, and the filtrate was distilled under reduced pressure at 80°C for 17 hours. The obtained solid was vacuum dried at 75°C for 20 hours to obtain lithium pyroxetate crystals. The yield was 97%.

[0035] The high temperature cycle stability, rate performance and low temperature performance of lithium benzene tetracarboxylate were tested in a 4.5V NCM811 / graphite soft pack battery system. The lithium battery electrolyte solvent is 30wt% DMC+25wt% DEC, the electrolyte is lithium hexafluorophosphate, the content is 30wt%-40wt%, and the content of the additive lithium benzene tetracarboxylate is 1.5%. It was compared with the additives available on the market (1.5% VC, 1.5% VC+1.5% FEC, 1.5% VC+2% 1,3PS). The battery of Example 6 with lithium benzene tetracarboxylate added has a capacity retention rate of 86.1% after 300 cycles at 50°C, while that of Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC+1.5% FEC), and Comparative Example 7 (1.5% VC+2% 1,3PS) are only 73.4%, 78.5%, and 79.2%, respectively; the battery of Example 6 with lithium benzene tetracarboxylate added has a 5C discharge capacity of 184.3 mAh / g, while that of Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC+1.3PS) are only ...6 (1.5% VC+1.3PS) are only 184.3 mAh / g, while that of Comparative Example 6 (1.5% VC+1.3PS) are only 184.3 mAh / g, while that of Comparative Example 6 (1.5% VC+1.3PS) are only 184.3 mAh / g, 5% FEC), Comparative Example 7 (1.5% VC+2% 1,3PS) are only 152.1mAh / g, 171.3mAh / g, and 173.5mAh / g, respectively; the 0.5C-20℃ discharge capacity retention rate of the battery in Example 6 with the addition of lithium phenyltetracarboxylate reaches 85.5%, while that of Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC+1.5% FEC), and Comparative Example 7 (1.5% VC+2% 1,3PS) are only 65.2%, 71.4%, and 71.7%, respectively. Comparative Example 1

[0036] Dissolve 1 mol of pyromellitic acid in ethylene glycol to prepare a 0.2 mol / L pyromellitic acid ethylene glycol solution. Add 3.8 mol of lithium hydroxide under stirring at 70°C, react for 20 hours, filter, and obtain crude lithium pyromellitic acid;

[0037] 100g of crude lithium pyromellitic acid was added to 1000ml of ethanol and dissolved under stirring at 70℃ for 2h, filtered while hot, and the filtrate was distilled at 60℃ for 12h under reduced pressure. The obtained solid was vacuum dried at 70℃ for 16h to obtain lithium pyromellitic acid crystals. The yield was 96%. The yield was calculated as the mass of lithium pyromellitic acid crystals (after purification): theoretically 1 mol of pyromellitic acid corresponds to the mass (yield) of lithium pyromellitic acid.

[0038] The high temperature cycle stability, rate performance and low temperature performance of lithium benzene tetracarboxylate were tested in a 4.5V NCM811 / graphite soft pack battery system. The lithium battery electrolyte solvent is 30wt% DMC+25wt% DEC, the electrolyte is lithium hexafluorophosphate, the content is 30wt%-40wt%, and the content of the additive lithium benzene tetracarboxylate is 1.5%. It was compared with the additives available on the market (1.5% VC, 1.5% VC+1.5% FEC, 1.5% VC+2% 1,3PS). In Example 1, the battery with lithium benzene tetracarboxylate added has a capacity retention rate of 87.6% after 300 cycles at 50°C, while that of Comparative Example 1, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) is only 85.2%, 73.4%, 78.5%, and 79.2%, respectively; the battery with lithium benzene tetracarboxylate added in Example 1 has a 5C discharge battery capacity of 186.5 mAh / g, while that of Comparative Example 1, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) is only 181.5 mAh / g, 152.1 mAh / g, 171.3 mAh / g, and 173.5 mAh / g, respectively; the battery with lithium benzene tetracarboxylate added in Example 1 has a capacity retention rate of 87.6% after 300 cycles at 50°C, while that of Comparative Example 1, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) is only 85.2%, 73.4%, 78.5%, and 79.2%, respectively; the battery with lithium benzene tetracarboxylate added in Example 1 has a capacity retention rate of 186.5 mAh / g at 5C discharge, while that of Comparative Example 1, Comparative Example 5 (1.5% VC), Comparative Example 6 (1. The -20℃ discharge capacity retention rate reached 85.2%, while that of Comparative Example 1, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC+1.5% FEC), and Comparative Example 7 (1.5% VC+2% 1,3PS) were only 82.6%, 65.2%, 71.4%, and 71.7%, respectively. Comparative Example 2

[0039] Dissolve 1 mol of pyromellitic acid in ethylene glycol to prepare a 0.3 mol / L pyromellitic acid ethylene glycol solution. Add 4.2 mol of lithium hydroxide under stirring at 60°C, react for 18 hours, filter, and obtain crude lithium pyromellitic acid;

[0040] 100g of crude lithium benzene tetracarboxylate was added to 2000ml of ethanol and dissolved under stirring at 90℃ for 1h, filtered while hot, and the filtrate was distilled at 80℃ for 20h under reduced pressure. The solid was vacuum dried at 90℃ for 24h to obtain lithium benzene tetracarboxylate crystals. The yield was 96%. Lithium benzene tetracarboxylate was tested for high temperature cycle stability, rate performance and low temperature performance in a 4.5V NCM811 / graphite soft pack battery system. Among them, the lithium battery electrolyte solvent was 30wt%DMC+25wt%DEC, the electrolyte was lithium hexafluorophosphate, the content was 30wt%-40wt%, and the content of the additive lithium benzene tetracarboxylate was 1.5%. And compared with the additives available on the market (1.5%VC, 1.5%VC+1.5%FEC, 1.5%VC+2%1,3PS). In Example 2, the battery with lithium benzene tetracarboxylate added has a capacity retention rate of 88.5% after 300 cycles at 50°C, while the capacity retention rate of Comparative Example 2, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) is only 84.3%, 85.2%, 73.4%, 78.5%, and 79.2%, respectively; the battery with lithium benzene tetracarboxylate added in Example 2 has a 5C discharge battery capacity of 179.3 mAh / g, while the capacity retention rate of Comparative Example 2, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) is only 179.3 mAh / g, 152.1 mAh / g, 171.3 mAh / g, and 173.5 mAh / g, respectively; the battery with lithium benzene tetracarboxylate added in Example 2 has a 0.5C discharge battery capacity of 179.3 mAh / g, while the capacity retention rate of Comparative Example 2, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) is only 179.3 mAh / g, 152.1 mAh / g, 171.3 mAh / g, and 173.5 mAh / g, respectively. The -20℃ discharge capacity retention rate reached 86.5%, while that of Comparative Example 2, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC+1.5% FEC), and Comparative Example 7 (1.5% VC+2% 1,3PS) were only 81.5%, 65.2%, 71.4%, and 71.7%, respectively. Comparative Example 3

[0041] Dissolve 1 mol of pyromellitic acid in ethylene glycol to prepare a 0.4 mol / L pyromellitic acid ethylene glycol solution. Add 4 mol of lithium hydroxide under stirring at 160°C, react for 38 seconds, filter, and obtain crude lithium pyromellitic acid;

[0042] 100 g of crude lithium pyroxetate was added to 1500 ml of ethanol and dissolved under stirring at 70°C for 1.5 h, filtered while hot, and the filtrate was distilled under reduced pressure at 70°C for 16 h. The obtained solid was vacuum dried at 80°C for 20 h to obtain lithium pyroxetate crystals. The yield was 98%.

[0043] The high temperature cycle stability, rate performance and low temperature performance of lithium benzene tetracarboxylate were tested in a 4.5V NCM811 / graphite soft pack battery system. The lithium battery electrolyte solvent is 30wt% DMC+25wt% DEC, the electrolyte is lithium hexafluorophosphate, the content is 30wt%-40wt%, and the content of the additive lithium benzene tetracarboxylate is 1.5%. It was compared with the additives available on the market (1.5% VC, 1.5% VC+1.5% FEC, 1.5% VC+2% 1,3PS). In Example 3, the battery with lithium benzenetetracarboxylate added has a capacity retention rate of 91.3% after 300 cycles at 50°C, while the capacity retention rate of Comparative Example 3, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) is only 85.5%, 85.2%, 73.4%, 78.5%, and 79.2%, respectively; the battery with lithium benzenetetracarboxylate added in Example 3 has a 5C discharge battery capacity of 195.9 mAh / g, while the capacity retention rate of Comparative Example 3, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) is only 180.9 mAh / g, 152.1 mAh / g, 171.3 mAh / g, and 173.5 mAh / g, respectively; the battery with lithium benzenetetracarboxylate added in Example 3 has a 0.5C discharge battery capacity of 195.9 mAh / g, while the capacity retention rate of Comparative Example 3, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) is only 180.9 mAh / g, 152.1 mAh / g, 171.3 mAh / g, and 173.5 mAh / g, respectively The -20℃ discharge capacity retention rate reached 88.6%, while that of Comparative Example 3, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC+1.5% FEC), and Comparative Example 7 (1.5% VC+2% 1,3PS) were only 82.4%, 65.2%, 71.4%, and 71.7%, respectively. Comparative Example 4

[0044] Dissolve 1 mol of pyromellitic acid in ethylene glycol to prepare a 0.2 mol / L pyromellitic acid ethylene glycol solution. Add 4 mol of lithium hydroxide under stirring at 180°C, react for 38 hours, filter, and obtain crude lithium pyromellitic acid;

[0045] 100 g of crude lithium pyroxetate was added to 1600 ml of ethanol and dissolved under stirring at 90°C for 3 hours, the filtrate was distilled under reduced pressure at 80°C for 16 hours, and the obtained solid was vacuum dried at 75°C for 18 hours to obtain lithium pyroxetate crystals with a yield of 99%.

[0046] The high temperature cycle stability, rate performance and low temperature performance of lithium benzene tetracarboxylate were tested in a 4.5V NCM811 / graphite soft pack battery system. The lithium battery electrolyte solvent is 30wt% DMC+25wt% DEC, the electrolyte is lithium hexafluorophosphate, the content is 30wt%-40wt%, and the content of the additive lithium benzene tetracarboxylate is 1.5%. It was compared with the additives available on the market (1.5% VC, 1.5% VC+1.5% FEC, 1.5% VC+2% 1,3PS). In Example 4, the battery with lithium benzene tetracarboxylate added has a capacity retention rate of 92.6% after 300 cycles at 50°C, while the capacity retention rates of Comparative Example 4, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) are only 83.8%, 73.4%, 78.5%, and 79.2%, respectively; the battery with lithium benzene tetracarboxylate added in Example 4 has a 5C discharge battery capacity of 196.8 mAh / g, while the capacity retention rates of Comparative Example 4, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) are only 178.4 mAh / g, 152.1 mAh / g, 171.3 mAh / g, and 173.5 mAh / g, respectively; the battery with lithium benzene tetracarboxylate added in Example 4 has a 0.5C discharge battery capacity of 196.8 mAh / g, while the capacity retention rates of Comparative Example 4, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) are only 178.4 mAh / g, 152.1 mAh / g, 171.3 mAh / g, and 173.5 mAh / g, respectively. The -20℃ discharge capacity retention rate reached 89.2%, while that of Comparative Example 4, Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC+1.5% FEC), and Comparative Example 7 (1.5% VC+2% 1,3PS) were only 81.3%, 65.2%, 71.4%, and 71.7%, respectively. Comparative Example 5

[0047] The VC in this comparative example was purchased from the market, the manufacturer is McLean, the purity is 98%, and the brand is CAS872-36-6. Similarly, the high temperature cycle stability, rate performance and low temperature performance tests were carried out in the 4.5V NCM811 / graphite soft pack battery system. The lithium battery electrolyte solvent is 30wt% DMC+25wt% DEC, the electrolyte is lithium hexafluorophosphate, the content is 30wt%-40wt%, and the additive VC content is 1.5%. Comparative Example 6

[0048] This comparative example uses a combination of 1.5% VC + 1.5% FEC. FEC is purchased from the market. The manufacturer is Shangfu Technology, with a purity of 99% and a brand name of 114435-02-8. Similarly, high temperature cycle stability, rate performance and low temperature performance tests were carried out on a 4.5V NCM811 / graphite soft pack battery system. The lithium battery electrolyte solvent is 30wt% DMC + 25wt% DEC, the electrolyte is lithium hexafluorophosphate, the content is 30wt%-40wt%, and the additive content is 1.5% VC + 1.5% FEC. Comparative Example 7

[0049] This comparative example uses a combination of 1.5% VC + 2% 1,3PS. 1,3PS is purchased from the market. The manufacturer is Jihechang, with a purity of 99.9% and a brand of 1120-71-4. Similarly, high-temperature cycle stability, rate performance and low-temperature performance tests are carried out on a 4.5V NCM811 / graphite soft-pack battery system. The lithium battery electrolyte solvent is 30wt% DMC + 25wt% DEC, the electrolyte is lithium hexafluorophosphate, the content is 30wt%-40wt%, and the additive content is 1.5% VC + 2% 1,3PS.

[0050]

[0051] It can be seen from Table 1 that the lithium pyrolytetracarboxylate obtained in each embodiment has high purity (>99.9%) and low impurity content (free acid <20ppm, water <25ppm, chloride ion <3ppm, sulfate ion <4ppm). The impurity content of the comparative example (synthesis reaction temperature and time are different from those of the embodiment) is higher than that of the embodiment, indicating that the reaction temperature and time of the present invention have better effects.

[0052] The purity of lithium benzene tetracarboxylate was tested by the nuclear magnetic resonance internal standard method. The internal standard was tetramethylsilane and the solvent was deuterated water. A small amount of lithium benzene tetracarboxylate and tetramethylsilane were dissolved in deuterated water to prepare the test solution. Then the test was performed to obtain 1 HNMR spectrum, and the purity of lithium pyrophthalate was obtained by internal standard method calculation formula.

[0053]

[0054] As can be seen from Table 2, the high temperature performance, rate performance and low temperature performance of the lithium benzene tetracarboxylate obtained in the embodiment are significantly higher than those of the comparative example. The capacity retention rate of the battery with lithium benzene tetracarboxylate added in Example 4 after 300 cycles at 50°C reached 92.6%, while that of Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC + 1.5% FEC), and Comparative Example 7 (1.5% VC + 2% 1,3PS) were only 73.4%, 78.5%, and 79.2%, respectively; the 5C discharge battery capacity of the battery with lithium benzene tetracarboxylate added in Example 4 reached 196.8 mAh / g, while that of Comparative Example 1 (1.5% VC), Comparative Example 2 (1.5% VC + 1.5% FEC), and Comparative Example 3 (1.5% VC + 2% 1,3PS) were only 152.1 mAh / g, 171.3 mAh / g, and 173.5 mAh / g, respectively; the 0.5C discharge battery capacity of the battery with lithium benzene tetracarboxylate added in Example 4 reached 196.8 mAh / g, while that of Comparative Example 1 (1.5% VC), Comparative Example 2 (1.5% VC + 1.5% FEC), and Comparative Example 3 (1.5% VC + 2% 1,3PS) were only 152.1 mAh / g, 171.3 mAh / g, and 173.5 mAh / g, respectively. The -20℃ discharge capacity retention rate reached 89.2%, while that of Comparative Example 5 (1.5% VC), Comparative Example 6 (1.5% VC+1.5% FEC), and Comparative Example 7 (1.5% VC+2% 1,3PS) were only 65.2%, 71.4%, and 71.7%, respectively. Moreover, the battery performance of the embodiment with the addition of lithium pyrophthalate is better than that of Comparative Examples 1-4 (the synthesis reaction temperature and time are different from those of the embodiment). This shows that the reaction temperature and time of the present invention are more effective. It also shows that the lithium pyrophthalate of the present invention has better performance as a lithium battery additive than the additives currently commonly used on the market.

[0055] Figure 1 is the H-NMR spectrum of lithium pyrophthalate of Example 4. Figure 1 The results of H NMR spectrum showed two absorption peaks at 4.79ppm and 7.50ppm, of which 4.79ppm was attributed to the deuterated solvent heavy water and 7.50ppm was attributed to lithium benzenetetracarboxylate. The H NMR spectrum only had one group of lithium benzenetetracarboxylate signals, proving that the product was very pure and did not contain other organic impurities.

[0056] Figure 2 This is the thermogravimetric spectrum of lithium benzenetetracarboxylate in Example 4. From the thermogravimetric graph, it can be seen that the lithium benzenetetracarboxylate sample starts to lose weight at about 130°C, and the weight decreases by 1.90% at about 400°C, and the weight decreases by 34.73% at about 620°C, and the lithium benzenetetracarboxylate decomposes. This proves that the lithium benzenetetracarboxylate has no water molecules and is very pure.

Claims

1. A method for preparing lithium pyromellitic acid, characterized in that: The following steps are involved: (1) under heating and stirring conditions, lithium hydroxide is added to an ethylene glycol solution of 0.2-0.4 mol / L pyromellitic acid, the heating reaction temperature is 100-120°C, the reaction time is 28-32 hours, the reaction solution is filtered to obtain a crude lithium pyromellitic acid product, wherein the molar ratio of pyromellitic acid to lithium hydroxide is 1:3.8-4.2; (2) dissolving the crude lithium pyroxene tetracarboxylate in ethanol under heating and stirring conditions, filtering while hot, distilling the filtrate under reduced pressure, and vacuum drying the obtained solid to obtain lithium pyroxene tetracarboxylate crystals; In the step (2), the ratio of crude lithium pyrolysis acid salt to ethanol is 1 g: 10-20 ml, the heating and stirring temperature is 70°C-90°C, and the time is 1-3 h; the temperature of the reduced pressure distillation is 60-80°C, and the time is 12-20 h; the temperature of the vacuum drying is 70-90°C, and the vacuum drying time is 16-24 h.

Citation Information

Patent Citations

  • Preparation method of naphthyl polycarboxylate organic material and application of naphthyl polycarboxylate organic material in metal ion battery

    CN115954444A

Cited By

  • Preparation method of sodium battery additive and application of sodium battery additive in sodium battery

    CN120904038A